(untitled) (Experimental biology, 2018)
It was identified 128 genes involved in the development of arterial hypertension and binding there mRNAs with miRNAs was studied. It was found 189 binding sites for 82 miRNAs. The changes in expression of 25 microRNAs which were found their target genes were found. From thus, 48 binding sites are located in the CDS, 18 - in the 5’UTR and 122 - in the 3’UTR. Some miRNAs have multiple binding sites with mRNA of genes participating in the development of arterial hypertension. miR-1273e has three binding sites with F11R gene mRNA, miR-466 - five binding sites with CD36 gene mRNA and six binding sites with MYADM gene mRNA, miR-574-5p has nine binding sites with IGF1 gene mRNA, miR-3960 - five sites with ADRB1 gene mRNA and four sites for PDE4D gene mRNA, miR-762 - four binding sites with STK39 gene mRNA. miR-619-5p binds with CACNB2 and CD36 genes mRNA with ΔG/ΔGm value equal to 100%, miR-3960, miR-1273e, miR-1273g-3p, miR-5095, miR-3665, miR-1273f binds with ADRB1, BMPR2, GSTM3, F11R, ICAM1, IGF1, LEP, MYADM, NEDD4L, TBXA2R genes with ΔG/ΔGm value equal to 98%. There was studied the binding of miRNAs with mRNAs of genes, participating in the development of arterial hypertension. It was identified 128 genes, participating in the development of arterial hypertension. It was found changes in expression of 25 microRNAs which were found their target genes in arterial hypertension. In mRNAs of genes involved in the development of arterial hypertension, it was identified 189 binding sites for 82 miRNAs. From thus, 48 binding sites are located in the CDS, 18 are located in the 5’UTR and 122 are located in the 3’UTR. Some miRNAs has multiple binding sites with mRNAs of genes, participating in the development of arterial hypertension. miR-1273e has three binding sites with mRNA of F11R, miR-466 has five binding sites with mRNA of CD36 gene and six binding sites with mRNA of MYADM gene, miR-574-5p has nine binding sites with mRNA of IGF1 gene, miR-3960 has five binding sites with mRNA of ADRB1 gene and four sites for mRNA of PDE4D gene, miR-762 has four binding sites with mRNA of STK39 gene. miR-619-5p binds with CACNB2 and CD36 genes, with ΔG/ΔGm value equal to 100%, miR-3960, miR-1273e, miR-1273g-3p, miR-5095, miR-3665, miR-1273f binds with ADRB1, BMPR2, GSTM3, F11R, ICAM1, IGF1, LEP, MYADM, NEDD4L, TBXA2R genes with ΔG/ΔGm value equal to 98%. The highest ΔG value is observed in the interaction of miR-6089 with mRNA of TGFB1 gene and equal to -136 kJ/mole. miR-762 binds with mRNA of STK39 gene with a ΔG value equal to -132 kJ/mole. miR-466 has four target genes: CD36, F11R, MYADM, ICAM1 with energy value from -104 kJ/mole to -108 kJ/mole and the ΔG/ΔGm value from 89% to 93% of the maximum free binding energy in miR-466-3p with the mRNA equal to -108 kJ/mole. miR-619-5p has 10 target genes: BMPR2, CACNB2, CD36, ECE1, F11R, GSTM3, LEP, MTHFR, MYADM, ROCK2 with a binding energy value from -110 kJ/mole to -119 kJ/mole and the ΔG/ΔGm value from 91% to 100% of the maximum free binding energy. Each of the target genes for miRNAs and each miRNA can significantly alter the rate of development of arterial hypertension.